Membrane structural biology : with biochemical and biophysical foundations - Luckey, Mary, 1948- (Cambridge ; New York : Cambridge University Press, 2014)
'This textbook provides a strong foundation and a clear overview for students of membrane biology and an invaluable synthesis of cutting edge research for working scientists. The text retains its clear and engaging style, providing a solid background in membrane biochemistry, while also incorporating the approaches of biophysics, genetics, and cell biology to investigations of membrane structure, function, and biogenesis to provide a unique overview of this fast-moving field. A wealth of new high resolution structures of membrane proteins are presented, including the Na/K pump and a receptor-G protein complex, offering exciting insights into how they function. All key tools of current membrane research are described, including detergents and model systems, bioinformatics, protein-folding methodology, crystallography and diffraction, and molecular modeling. This comprehensive and up-to-date text, emphasizing the correlations between membrane research and human health, provides a solid foundation for all those working in this field'--
Introduction -- The diversity of membrane lipids -- Tools for studying membrane components : detergents and model systems -- Proteins in or at the bilayer -- Bundles and barrels -- Functions and families -- Protein folding and biogenesis -- Diffraction and simulation -- Membrane enzymes -- Membrane receptors -- Transporters -- Channels -- Electron transport and energy transduction -- In pursuit of complexity.
Includes bibliographical references and index.
Keywords: Cell membrane -- Physiology; Membrane Lipids -- physiology; Membrane Proteins -- physiology